2019
DOI: 10.3390/antiox8120609
|View full text |Cite
|
Sign up to set email alerts
|

The Health-Promoting Potential of Salix spp. Bark Polar Extracts: Key Insights on Phenolic Composition and In Vitro Bioactivity and Biocompatibility

Abstract: Salix spp. have been exploited for energy generation, along with folk medicine use of bark extracts for antipyretic and analgesic benefits. Bark phenolic components, rather than salicin, have demonstrated interesting bioactivities, which may ensure the sustainable bioprospection of Salix bark. Therefore, this study highlights the detailed phenolic characterization, as well as the in vitro antioxidant, anti-hypertensive, Staphylococcus aureus growth inhibitory effects, and biocompatibility of Salix atrocinerea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Among other Salix species, S. atrocinerea and S. viminalis bark extracts exhibited similar activities in the DPPH test (EC 50 = 10.98 and 14.06 μg/mL, respectively) as in the present study. On the other hand, the bark extract of S. fragilis demonstrated lower activity (EC 50 = 23.62 μg/mL) [ 42 ]. The results of the ABTS assay are comparable with those achieved earlier for other willow species, including S. purpurea barks (EC 50 = 20 μg/mL) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other Salix species, S. atrocinerea and S. viminalis bark extracts exhibited similar activities in the DPPH test (EC 50 = 10.98 and 14.06 μg/mL, respectively) as in the present study. On the other hand, the bark extract of S. fragilis demonstrated lower activity (EC 50 = 23.62 μg/mL) [ 42 ]. The results of the ABTS assay are comparable with those achieved earlier for other willow species, including S. purpurea barks (EC 50 = 20 μg/mL) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In earlier studies, S. alba bark extract has demonstrated cytotoxic and genotoxic potential against different cell lines, for example the human leukemia (HL-60) cell line [ 6 ], human peripheral leukocyte cells and the human hepatoma cell line, with doses from 50 and 200 µg/mL [ 44 ]. However, other extracts from bark of S. atrocinerea and S. fragilis did not exert a cytotoxic effect (at 625 and 1250 µg/mL) against immortalized human keratinocytes (HaCaT) and mouse fibroblast (L929) cells [ 42 ]. The differences between cytotoxicity dose could be connected with differences in the solvent or cell line model.…”
Section: Resultsmentioning
confidence: 99%
“…Willow bark is listed in the European Pharmacopoeia [ 26 ] and due to its salicin content (precursor of aspirin), it has been traditionally used for treating fever, pain, and inflammation in humans. The bioactive phytomolecules, medicinal values, and nutritional properties of this plant have been extensively studied by previous researchers [ 27 , 28 , 29 , 30 ]. Salix bark is a rich and inexpensive source of phenolic glycosides [ 31 ] and polyphenols, such as flavonoids and condensed tannins [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salix bark is a rich and inexpensive source of phenolic glycosides [ 31 ] and polyphenols, such as flavonoids and condensed tannins [ 32 ]. These constituents are reported to possess antirheumatic, antipyretic, anti-inflammatory, hypoglycemic [ 33 ], antibacterial [ 34 ], and antioxidant activities [ 30 , 35 ]. Although willow has been extensively studied in vitro and its undeniable beneficial properties have been proven, few studies are found on its applications in animal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Willow bark is listed in the European Pharmacopoeia [26] and due to its salicin content (precursor of aspirin), it has been traditionally used for treating fever, pain, and inflammation in humans. The bioactive phytomolecules, medicinal values, and nutritional properties of this plant have been extensively studied by previous researchers [27][28][29][30]. Salix bark is a rich and inexpensive source of phenolic glycosides [31] and polyphenols, such as flavonoids and condensed tannins [32].…”
Section: Introductionmentioning
confidence: 99%